2022
DOI: 10.3390/ijms23169148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Circulating Tumor Cells, Urinary MicroRNA, and Urinary Cell-Free DNA for Bladder Cancer: A Review

Abstract: Early detection of primary bladder cancer (BCa) is vital, because stage and grade have been generally accepted not only as categorical but also as prognostic factors in patients with BCa. The widely accepted screening methods for BCa, cystoscopy and urine cytology, have unsatisfactory diagnostic accuracy, with high rates of false negatives, especially for flat-type BCa with cystoscopy and for low-risk disease with urine cytology. Currently, liquid biopsy has attracted much attention as being compensatory for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…ucfDNAs also gain attention due to their close contact with lesions of urinary disease and are therefore considered potential urine biomarkers for BC. 26,27 Recent clinical research found that ucfDNA can monitor the recurrence and progression of NMIBC. Xu et al 28 enrolled 103 patients with NMIBC (pTa-pT1) and measured the IQGAP3/BMP4 expression ratios in ucfDNA by real-time quantitative polymerase chain reaction (RT-qPCR).…”
Section: Cell-free Dna and Circulating Tumour Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…ucfDNAs also gain attention due to their close contact with lesions of urinary disease and are therefore considered potential urine biomarkers for BC. 26,27 Recent clinical research found that ucfDNA can monitor the recurrence and progression of NMIBC. Xu et al 28 enrolled 103 patients with NMIBC (pTa-pT1) and measured the IQGAP3/BMP4 expression ratios in ucfDNA by real-time quantitative polymerase chain reaction (RT-qPCR).…”
Section: Cell-free Dna and Circulating Tumour Dnamentioning
confidence: 99%
“…Currently, plasma cfDNA is widely explored for its potential in tumour detection. ucfDNAs also gain attention due to their close contact with lesions of urinary disease and are therefore considered potential urine biomarkers for BC 26,27 . Recent clinical research found that ucfDNA can monitor the recurrence and progression of NMIBC.…”
Section: The Presence Of Genomic Dna In Urine Of Bc Patientsmentioning
confidence: 99%
“…Liquid biopsy is based on the detection of circulating tumor cells (CTCs) and “cell-free” nucleic acids in blood and body fluids, including urine, saliva, tears, sweat, amniotic fluid, cerebrospinal and pleural fluids, and cervicovaginal secretions, to detect and quantify targets of interest [ 13 , 14 ]. Significant progress has been made in the detection of urinary biomarkers for BC, but it is currently limited by its low sensitivity and specificity [ 15 , 16 ]. Since blood is in contact with most tumors, liquid biopsies mainly involve blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the alteration of miRNAs has not been fully elucidated in the bladder, miRNAs are deregulated in bladder cancer and have been seen to promote cell proliferation and progression through epithelial-to-mesenchymal transition and inhibit apoptosis [ 15 , 16 ]. Therefore, thanks to their high stability in biological fluids, miRNAs represent one of the most promising biomarkers for cancer detection, including bladder cancer [ 17 ]. Here, we provide a systematic overview to collect and summarize the current state-of-the-art trials on urine miRNAs as promising biomarkers for a BC diagnosis.…”
Section: Introductionmentioning
confidence: 99%